EFFECT OF ADDITIONAL GUAVA (Psidium guajava) ON ORGANOLEPTICS PROPERTIES, PH VALUE, AND VITAMIN C LEVELS IN COWPEA YOGURT (Psidium guajava) - Chynthia Regina Wijaya; Diyan Yunanto setyaji; Rijantono Franciscus Maria (Journal of Global Nutrition, 2023)
Yogurt is a great source of probiotics and is claimed to be a healthy dietary supplement. Yogurt is usually made from animal sources. This study used yogurt made from vegetable protein sources such as cowpea. Cowpea is rich in protein but low in vitamin C. Guava is added to yogurt as a source of vitamin C. This study aims to determine the effect of adding guava juice on organoleptic properties including color, taste, texture, aroma, after taste, and overall preference, pH value, and vitamin C of cowpea yogurt. Experimental research was conducted with a completely randomized design (CRD) in the control sample group (P0) and three sampels with the addition of guava 10% (P1), 20% (P2), and 30% (P3). Organoleptic properties were analyzed by Friedman test and continued by Wilcoxon test. The pH and vitamin C values were analyzed descriptively. The results showed that the highest scores for the color and taste parameters were obtained from the group with the addition of 30% guava with a score of 4.43±0.68 and 3.80±0.81 respectively. The highest score for the aroma parameter of 3.63±0.89 was obtained from the group with the addition of 20% guava. The group with the addition of 30% guava got the highest score for the overall preference parameter with a score of 3.67±1.06. Each sample group has a texture and aftertaste that is not statistically significant. The increase in giving guava to cowpea yogurt caused the pH value to decrease, the acidity level to increase, and vitamin C levels to decrease. It can be concluded that the addition of guava affects the parameters of color, taste, aroma, overall preference, lowers the pH value, but does not affect the parameters of texture, after taste, and does not increase the vitamin C content of cowpea yogurt. Keywords: cowpea yogurt, guava, organoleptic properties, pH, vitamin C